Food and nutritional security: knowledge and actions of nurses of the Family Health Program for patients with chronic illnesses - doi:10.5020/18061230.2009.p194 - Sandra Mara Pimentel Duavy Pereira; Maria Augusta Vasconcelos Palácio; José Evaldo Gomes Júnior; Willys da Silva Santos (Universidade de Fortaleza, 2012)
Objective: To identify the knowledge on basic notions and the actions of Food and Nutritional Security (FNS) developed by nurses of the Family Health Program (FHP) of a city in Ceará to patients with chronic illnesses. Methods: A descriptive, exploratory and quantitative study, in which all the nurses (n=27) from the FHP of the selected city were studied, in the period of June to August, 2008. A structured interview was applied and the data were categorized by descriptive analysis establishing the following variables: general notions on FNS and the development of actions of FNS. Later, the frequency of the answers for each category was determined. Results: It was observed that 9 (33.3%) subjects did not have basic notions on FNS. As for the development of actions referring to FNS, they all performed dietary guidance and 13 (48.1%) also carried out activities of health education, such as the formation of groups of diabetic and hypertensive patients. Difficulties were referred for not accomplishing these activities, amongst which, the low socioeconomic conditions of the patients and the lack of time of the professionals. Conclusion: It was perceived the need for disclosing general information on FNS among the nurses of the FHP of the studied city, as well as actions that surpass the dietary guidelines prevalent in the study and that envisage measures to prevent and control these chronic illnesses.